2008
DOI: 10.1242/jeb.015131
|View full text |Cite
|
Sign up to set email alerts
|

Diapause in tardigrades: a study of factors involved in encystment

Abstract: SUMMARYStressful environmental conditions limit survival, growth and reproduction, or these conditions induce resting stages indicated as dormancy. Tardigrades represent one of the few animal phyla able to perform both forms of dormancy: quiescence and diapause. Different forms of cryptobiosis (quiescence) are widespread and well studied, while little attention has been devoted to the adaptive meaning of encystment (diapause). Our goal was to determine the environmental factors and token stimuli involved in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 24 publications
0
27
0
1
Order By: Relevance
“…A peculiar finding was the amplification of the tps gene in the limnic species Dactylobiotus parthenogeneticus, which was not able to survive desiccation (Table III) (Powell et al 1986a,b;Wienkem 1990;Becker et al 1996), as a defence against reactive oxygen species (Banaroudj et al 2001;França et al 2007), and in the regulation process of different biological functions, such as moulting (Chung 2008). In tardigrades moulting is strictly correlated with encystment, a diapause stage involving a reduction in metabolism, the loss of a small amount of body water, and the synthesis of several new cuticular layers without ecdysis (Guidetti et al 2006(Guidetti et al , 2008. Considering that D. parthenogeneticus is a limnic species able to encyst (Guidetti et al 2006, the most probable scenario could be that trehalose is involved in the regulation of the encystment process.…”
Section: Discussionmentioning
confidence: 99%
“…A peculiar finding was the amplification of the tps gene in the limnic species Dactylobiotus parthenogeneticus, which was not able to survive desiccation (Table III) (Powell et al 1986a,b;Wienkem 1990;Becker et al 1996), as a defence against reactive oxygen species (Banaroudj et al 2001;França et al 2007), and in the regulation process of different biological functions, such as moulting (Chung 2008). In tardigrades moulting is strictly correlated with encystment, a diapause stage involving a reduction in metabolism, the loss of a small amount of body water, and the synthesis of several new cuticular layers without ecdysis (Guidetti et al 2006(Guidetti et al , 2008. Considering that D. parthenogeneticus is a limnic species able to encyst (Guidetti et al 2006, the most probable scenario could be that trehalose is involved in the regulation of the encystment process.…”
Section: Discussionmentioning
confidence: 99%
“…Encystment represents one of the enigmatic dormancy states of tardigrades and the causes of its induction and evolution remain still unclear (Guidetti et al 2008). Even though several morphological changes occur during the encystment process ) almost nothing is known about its physiology.…”
Section: Discussionmentioning
confidence: 99%
“…For the first time, our data revealed that both Hsp70 and Hsp90 are not up-regulated in encysted specimens of B. volubilis with respect to desiccated or hydrated specimens. This absence could be due to the fact that tardigrades undergo encystment in advance to environmental adversities (Guidetti et al 2008) so they probably are not in a stressed state facing stressful conditions that need high level of Hsps. To protect themselves from the coming environmental stresses (related to summer period), and therefore to maintain their homeostasis, the tardigrade cysts minimize exchange with their environment by remaining within their old cuticles (exuvia) and producing further cuticular layers .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations